Interpreting Physics Language and the Classical/Quantum Divide - MacKinnon, Edward; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
This book is the first to offer a systematic account of the role of language in the development and interpretation of physics. An historical-conceptual analysis of the co-evolution of mathematical and physical concepts leads ti the classical/quatum interface. Bohrian orthodoxy stresses the indispensability of classical concepts and the functional role of mathematics. We analyze ways of extending and then going beyond this orthodoxy orthodoxy. Finally, the book analyzes how a revised interpretation of physics impacts on basic philosophical issues: conceptual revolutions, realism, and reductionism.
Preface -- 1. A Philosphical Overview -- 2. From Categories to Quantative Concepts,- 3. The Unification of Classical Physics -- 4. Classical Physics -- 5. Orthodox Quantum Mechanics -- 6. Beyond a Minimal Basis -- 7. Interpreting Physics.
Keywords: Philosophy (General).; Science -- History; Science -- Philosophy; Physics; Philosophy; Philosophy of Science; Physics, general; History of Science